Recombinant allergens for pollen immunotherapy. (December 2013) - Wallner, Michael; Pichler, Ulrike; Ferreira, Fatima
Specific immunotherapy (IT) represents the only potentially curative therapeutic intervention of allergic diseases capable of suppressing allergy-associated symptoms not only during treatment, but also after its cessation. Presently, IT is performed with allergen extracts, which represent a heterogeneous mixture of allergenic, as well as nonallergenic, compounds of a given allergen source. To overcome many of the problems associated with extract-based IT, strategies based on the use of recombinant allergens or derivatives thereof have been developed. This review focuses on recombinant technologies to produce allergy therapeuticals, especially for allergies caused by tree, grass and weed pollen, as they are among the most prevalent allergic disorders affecting the population of industrialized societies. The reduction of IgE-binding of recombinant allergen derivatives appears to be mandatory to increase the safety profile of vaccine candidates. Moreover, increased immunogenicity is expected to reduce the dosage regimes of the presently cumbersome treatment. In this regard, it has been convincingly demonstrated in animal models that hypoallergenic molecules can be engineered to harbor inherent antiallergenic immunologic properties. Thus, strategies to modulate the allergenic and immunogenic properties of recombinant allergens will be discussed in detail. In recent years, several successful clinical studies using recombinant wild-type or hypoallergens as active ingredients have been published and, currently, novel treatment forms with higher safety and efficacy profiles are under investigation in clinical trials. These recent developments are summarized and discussed.